Teori Kedatangan dan Perkembangan Islam serta Penyebarannya di Indonesia dan Malaysia - Nisfil Mukaromah; Kholid Mawardi (STIKes Ibnu Sina Ajibarang, 2026)
Islam in Southeast Asia, particularly in Indonesia and Malaysia, has developed through a unique and peaceful process compared to other Muslim regions. This study examines the theories of the arrival of Islam and its development and dissemination in Indonesia and Malaysia. The research aims to analyze various perspectives regarding the origins of Islam in Southeast Asia and to describe the factors and characteristics of Islamic development in both countries. This research adopts a descriptive qualitative approach, utilizing a literature study to examine relevant books., journals, and historical documents related to the Islamization process in Southeast Asia. The findings indicate that the arrival of Islam in the region is explained through several theories, namely the Gujarat, Arab, Persian, Chinese, and multi-route theories. Furthermore, the spread of Islam was influenced by trade, marriage, Sufism, education, and political factors. In Indonesia and Malaysia, Islam developed peacefully, adapted to local cultures, and became an important element in social, cultural, educational, and political life. The study concludes that Islam in Southeast Asia has distinctive characteristics, including moderation, tolerance, cultural accommodation, and a strong educational tradition, making it a model of inclusive Islamic civilization in the contemporary world.